Esensi Kesadaran Masyarakat Terhadap Hukum Menuju Momentum Pemilihan Kepala Daerah Tahun 2024 - Darmun, Darmun; Khuluq, Nabil Husnul; Fiqih, Ahmad; Taufiqurrahman, Taufiqurrahman; Komala, Lidy A Nur (Prosiding Seminar Nasional Pengabdian Masyarakat, 2024)
Indonesia is a democratic country with the principle of from the people by the people for the people, this principle is implemented in Regional Head Elections. However, there are still many people who do not understand the importance of democracy and legal awareness. Public awareness of the law towards the momentum of regional elections in 2024 aims to increase public participation in the success of the national agenda of the Republic of Indonesia in their respective regions. By integrating the concept of national spirit and the empirical approach method, this method directly involves the community in increasing legal awareness which is one of the important elements in the life of the nation and state. Making the character of a mature society understand its rights and obligations as an Indonesian citizen.